2009
DOI: 10.1021/es802985e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Synaptic Transmission, Calcium Current, and Neurite Growth by Perfluorinated Compounds Are Dependent on the Chain Length and Functional Group

Abstract: Scientific and public concerns on perfluorinated compounds (PFCs) are increasingly growing because of their environmental persistency, bioaccumulation, and extensive distribution throughout the world. Little is known about the effects of PFCs on neural function and the underlying mechanisms. Recent evidence suggests that the toxicological effects of PFCs are closely correlated with their carbon chain lengths. In this present work, the actions of PFCs with varying chain length on cultured rat hippocampal neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 32 publications
2
46
0
2
Order By: Relevance
“…Because the acute oral convulsive dose of PFOS was 250 mg/kg , the convulsion induced by PFOS seemed to depend on its total dose regardless of treatment schedule. The information provided by Liao et al (2009), that the potency on increases in the frequencies of spontaneous mPSC of perfluorinated carboxylates was less pronounced than that of perfluorinated sulfonates, is supportive to this PFOS-specific neurotoxicity. Kawamoto et al (2008) reported as follows: PFOS (15 μM or higher) but not PFOA caused backward swimming of paramecia, which was induced by intracellular free Ca2 + at 0.2 μM and higher.…”
Section: Animal Studiesmentioning
confidence: 80%
See 3 more Smart Citations
“…Because the acute oral convulsive dose of PFOS was 250 mg/kg , the convulsion induced by PFOS seemed to depend on its total dose regardless of treatment schedule. The information provided by Liao et al (2009), that the potency on increases in the frequencies of spontaneous mPSC of perfluorinated carboxylates was less pronounced than that of perfluorinated sulfonates, is supportive to this PFOS-specific neurotoxicity. Kawamoto et al (2008) reported as follows: PFOS (15 μM or higher) but not PFOA caused backward swimming of paramecia, which was induced by intracellular free Ca2 + at 0.2 μM and higher.…”
Section: Animal Studiesmentioning
confidence: 80%
“…PFOS induced cell membrane excitability, and the action potential of the paramecium was induced at lower current intensity with PFOS. The ultrasonic-induced fatal tonic convulsion of rodents might be related to the PFOS-specific cell membrane excitability shown by Liao et al (2009) and Kawamoto et al (2008).…”
Section: Animal Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Potential health effects in animal models have been reported by several authors [8]. PFASs are also considered endocrine disrupting chemicals (EDCs), with a particular debate related to their possible impact on reproductive functions in man [9][10][11]. PFOA and PFOS have been linked to disorders in homeostatic sexuality hormones and have been associated with the increase of fetal resorptions and abortions in animals.…”
mentioning
confidence: 99%